1985
DOI: 10.1002/macp.1985.021860902
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of poly(phthalidylidenearylene)s

Abstract: The structure of poly(phthalidylidenearylene)s, synthesized by electrophilic substitution reactions, was studied using 'H and 13C NMR spectroscopy. Homopolycondensation of 3-aryl-3chlorophthalides 1 ad in nitrobenzene leads to para-substituted linear polymers 2ad, whereas polycondensation of phthaloyl dichloride and bis[4-(3-chloro-3-phthalidyl)phenyl] ether (6) with diphenyl ether results in polymers 5 containing irregular units. 0025-1 16X/85/%03.00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The present work was aimed at a polymer synthesis via homopolycondensation of 3-aryl-3-chlorophthalides 3a-c, 4 and 5, containing substituents in the benzene ring of the phthalide cycle. The initial monomers were prepared on the basis of related substituted phthalide anhydrides 3a: m.p.…”
Section: Introductionmentioning
confidence: 99%
“…The present work was aimed at a polymer synthesis via homopolycondensation of 3-aryl-3-chlorophthalides 3a-c, 4 and 5, containing substituents in the benzene ring of the phthalide cycle. The initial monomers were prepared on the basis of related substituted phthalide anhydrides 3a: m.p.…”
Section: Introductionmentioning
confidence: 99%
“…Their properties can be controlled by changing the structure of the bridged phenyl fragments . Homo‐poly(arylenphthalide), containing diphenyl, diphenyl oxide, diphenyl sulfide and fluorene fragments, as well as regularly alternating and sequentially ordered poly(arylenphthalide) periodic structures with terphenyl and diphenyl oxide fragments in the main chain were studied earlier with NMR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, 13 С NMR techniques allowed studying both the polycondensation of 3‐chlorophthalides (phthaloyl dichlorides) with aromatic (heteroaromatic) hydrocarbons and the homopolycondensation of 3‐aryl‐3‐chlorophthalides . The structure of the generated poly(arylenephthalide) derivatives has been elucidated, and it was shown that depending on the type of chloranhydrate and on the reaction conditions, the electrophilic attack of the aromatic hydrocarbon can occur both in para ‐position and meta ‐position.…”
Section: Introductionmentioning
confidence: 99%